Younger Dryas sea level and meltwater pulse 1B recorded in Barbados reef crest coral Acropora palmata - Abdul, N. A.; Mortlock, R. A.; Wright, J. D.; Fairbanks, R. G. (Paleoceanography, 2016)
The Younger Dryas climate event occurred during the middle of the last deglacial cycle and is marked by an abrupt shift in the North Atlantic polar front almost to its former glacial position, trending east to west. Using high‐precision and high‐accuracy U‐Th‐dated Barbados reef crest coral, Acropora palmata, we generate a detailed sea level record from 13.9 to 9000 years before present (kyr B.P.) and reconstruct the ice volume response to the Younger Dryas cooling. From the mid‐Allerød (13.9 kyr B.P.) to the end of the Younger Dryas (11.65 kyr B.P.), rates of sea level rise decreased smoothly from 20 mm yr−1 to 4 mm yr−1, culminating in a 400 year “slow stand” before accelerating into meltwater pulse 1B (MWP‐1B). The MWP‐1B event at Barbados is better constrained as beginning by 11.45 kyr B.P. and ending at 11.1 kyr B.P. during which time sea level rose 14 ± 2 m and rates of sea level rise reached 40 mm yr−1. We propose that MWP‐1B is the direct albeit lagged response of the Northern Hemisphere ice sheets to the rapid warming marking the end of the Younger Dryas coinciding with rapid warming in the circum‐North Atlantic region and the polar front shift from its zonal to meridional position 11.65 kyr B.P. As predicted by glaciological models, the ice sheet response to rapid North Atlantic warming was lagged by 400 years due to the thermal inertia of large ice sheets. The regional circum‐North Atlantic Younger Dryas climate event is elevated to a global response through sea level changes, starting with the global slowdown in sea level rise during the Younger Dryas and culminating with MWP‐1B. No meltwater pulses are evident at the initiation of the Younger Dryas climate event as is often speculated. Key Points Barbados A. palmata SL record shows no evidence that a MWP triggered the Younger Dryas A. palmata record rate of SL rise decreased smoothly to a “slow stand” by Younger Dryas' end MWP‐1B confirmed as a 14 {+ or ‐} 2 m jump in SL coincident with North Hemisphere insolation maximum